The Effects of Using a Guidance Activities Package to Develop Stress Management Ability of Mathayom Suksa V Students at Datdaruni School in Chachoengsao Province - Chooseng, Suwadee; Sansa, Niranart; Sabaiying, Wunlapa (Ratchaphruek Journal, 2020)
The objectives of this research were (1) to compare the levels of stress management ability of students in the experimental group before and after using a guidance activities package to develop stress management ability; and (2) to compare the stress management ability level of the experimental group students who used the guidance activities package to develop stress management ability with the counterpart ability level of the control group students who undertook traditional guidance activities. The research sample consisted of Mathayom Suksa V students in two intact classrooms of Datdaruni School in Chachoengsao province during the 2019 academic year. Then, one classroom containing 35 students was randomly assigned to be the experimental group; the other classroom containing 37 students, the control group. The employed research instruments were (1) a scale to assess stress management ability; (2) a guidance activities package to develop stress management ability; and (3) a set of traditional guidance activities. Statistics employed for data analysis were mean, standard deviation, and t-test. Research findings showed that (1) the post-experiment stress management ability level of the experimental group students who used the guidance activities package to develop stress management ability was significantly higher than their pre-experiment counterpart ability level at the .01 level of statistical significance; and (2) the post-experiment stress management ability level of the experimental group students who used the guidance activities package to develop stress management ability was significantly higher than the counterpart ability level of the control group students who undertook traditional guidance activities at the .01 level of statistical significance.